Vulvar vitiligo-like depigmentation and multiple halos of hypomelanosis at the trunk following treatment with imiquimod 5% cream for vulvar condylomata: casual or related events? - Maíra Chiarelli Serra; Claudia Menicanti; Elisabetta Pennacchioli; Giulio Tosti (Sociedade Brasileira de Dermatologia, 2014)
A 25-year-old Caucasian female with multiple genital warts involving the vulvar area was treated with imiquimod 5% cream. During follow-up the patient developed areas of hypopigmentation at the site of application of imiquimod cream and areas of hypomelanosis around multiple preexisting nevi of the trunk. At 18 months follow-up genital depigmentation persisted and halo nevi of the trunk were still present. Different mechanisms of imiquimod-induced depigmentation have been reported. Halo nevi are considered expression of an autoimmune response. In the case presented here, it might be conceivable that both vitiligo-like depigmentation at the site of application and halo of hypomelanosis around melanocytic nevi have been induced by the same immunologic mechanism elicited by topical application of imiquimod.